Compressive strength of concrete using rice husk ash produced at different temperatures / Abdalla. T.Z. Shawsh and Thevaneyan Krishta David - T.Z. Shawsh, Abdalla; Krishta David, Thevaneyan (2023)
This study focuses on the optimization of the burning temperature of furnace-incinerated rice husk ash (RHA) into a concrete mix design. The primary objective of this study is to investigate the optimum proportion of incineration temperature required to develop an amorphous silica from rice husk wastes and to determine the compressive strength of blended cement replaced partially at the ratio of 5%, 7.5%, 10.0%, and 12.5% of RHA, incinerated at temperatures of 600 °C, 700 °C, and 800 °C. The experimental test specimens, consisting of concrete cubes, were prepared and tested after 7, 14, and 28 days of water curing. The pozzolanic reactivity of RHA highly depends on the silica form. The silica form in the RHA is analyzed by chemical composition analysis and x-ray diffraction analysis based on the incineration period to decide if it is in the amorphous or crystalline form, with the identifying sample having a greater influence on the compressive strength. This study shows that the presence of RHA in concrete tends to improve compressive strength, especially at the early stages of curing, and the optimum replacement of cement with RHA in the concrete was 7.5% at the incineration temperature of 700 °C.